'Working While Feeling Awful Is Normal': One Roma's Experience of Presenteeism. (April 2022) - Collins, Helen; Barry, Susan; Dzuga, Piotr
This article presents an account of a young Roma man's lived experience of working in the agricultural sector while sick, and shines a spotlight on the impact of precarious work, low pay and eligibility, and access to sick pay, with particular emphasis on Roma, and how these factors interconnect to foster presenteeism. The repercussions of presenteeism, relayed through Piotr's personal narrative and reflections about his work, family role, ambition and daily survival, enrich public sociology about this under explored area of migrant Roma's working life.